2018
DOI: 10.1007/978-1-4939-7837-3_3
|View full text |Cite
|
Sign up to set email alerts
|

Growing Murine Bone Marrow-Derived Macrophages

Abstract: Bone marrow-derived macrophages (BMDM) are primary macrophages obtained by in vitro differentiation of bone marrow cells in the presence of macrophage colony-stimulating factor (M-CSF or CSF1). They are easy to obtain in high yields, can be stored by freezing, and can be obtained from genetically modified mice strains. They are therefore widely used as prototypical macrophages for in vitro studies. In this chapter, we present the method for obtaining BMDMs and freezing them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
54
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 3 publications
0
54
0
Order By: Relevance
“…Cultures were incubated at 37°C in a humidified atmosphere containing 5% CO 2 . Bone‐marrow–derived macrophages (BMDMs) were isolated and grown in DMEM supplemented with 10% FBS, 1% penicillin‐streptomycin, and 20 ng/mL of macrophage/colony‐stimulating factor as reported . After 7 days, BMDMs were ready for further experimentation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cultures were incubated at 37°C in a humidified atmosphere containing 5% CO 2 . Bone‐marrow–derived macrophages (BMDMs) were isolated and grown in DMEM supplemented with 10% FBS, 1% penicillin‐streptomycin, and 20 ng/mL of macrophage/colony‐stimulating factor as reported . After 7 days, BMDMs were ready for further experimentation.…”
Section: Methodsmentioning
confidence: 99%
“…Bone-marrow-derived macrophages (BMDMs) were isolated and grown in DMEM supplemented with 10% FBS, 1% penicillin-streptomycin, and 20 ng/mL of macrophage/colony-stimulating factor as reported. (21) After 7 days, BMDMs were ready for further experimentation. Peritoneal macrophages were isolated by anti-F4/80 microBeads (Miltenyi Biotec, Shanghai, China), according to the manufacturer's instructions.…”
Section: Cell Culturementioning
confidence: 99%
“…BMDMs are primary macrophages obtained from C57BL/6 mouse bone marrow of the tibia and femur as described previously [79]. Three mice were uesd for BMDM preparation in each individual experiment, three independent experiments were performed.…”
Section: Mice and Cell Culturementioning
confidence: 99%
“…The ow cytometric analysis revealed that the differentiation of BMDMs into TEMs in tumor-bearing mice was higher than that in wild-type mice. It is estimated that there are approximately 60 × 10 6 bone marrow cells in each mouse from which 30 × 10 6 BMDMs are generated [32]. The method established in this study enables the isolation of a large number of TEMs.…”
Section: Discussionmentioning
confidence: 99%